IDENTIFICATION STUDY OF MANAGEMENT PERFORMANCE INDICATORS BY PANDANREJO TOURISM VILLAGE MANAGEMENT - Brantas Brantas (SEAN Institute, 2023)
The significant roles and functions of community participation in management are a critical basis for the urgency of reviewing the performance of tourism village managers. This study was conducted at the Pandanrejo Tourism Village (Dewa Pandan). Through the performance indicators of tourism village management, it can be studied how these indicators are applied to the Pandanrejo Tourism Village, to find out the strengths, weaknesses, and factors that influence the performance of the Pandanrejo Tourism Village Pokdarwis. The study was carried out descriptively with a qualitative approach. Based on observations, interviews, and secondary data collection, it was found that Dewa Pandan had implemented management performance indicators well. However, there are still weaknesses in institutional performance as well as conservation performance.